Blood cell attachment to root surfaces treated with EDTA gel. - Leite, Fábio Renato Manzolli; Moreira, Camila Sala; Theodoro, Letícia Helena [UNESP]; Sampaio, José Eduardo Cezar [UNESP] (FapUNIFESP (SciELO), 2005)
Root debridement generates a smear layer which contains microorganisms and toxins that could interfere in periodontal healing. For this reason, different substances have been used to remove it and to expose collagen fibers at the tooth surface. Blood element adhesion to demineralized roots and clot stabilization by collagen fibers are extremely important for the success of periodontal surgery. The aim of this study was to evaluate the different patterns of blood element adsorption and adhesion to root surfaces only irrigated with distilled water and after application of a manipulated or an industrialized EDTA gel. Thirty samples were planed, equally divided into three groups and treated with distilled water (control), a manipulated EDTA gel or an industrialized one. Immediately after, samples were exposed to fresh blood and prepared for scanning electron microscopy. Untreated planed dentin presented the best results with blood cells entrapped in a thick web of fibrin. In the manipulated EDTA group, the web of fibrin was thick with sparse blood elements. The worst result was seen with the industrialized EDTA group, in which no blood elements could be seen. Statistical difference was obtained between control and industrialized EDTA groups. Surfaces only irrigated presented the most organized fibrin network and cell entrapment.
Keywords: chelating agent; edetic acid; adsorption; cell adhesion; comparative study; dental surgery; dentin; drug effect; endodontics; gel; human; methodology; nonparametric test; physiology; preventive dentistry; tooth root; ultrastructure; Adsorption; Cell Adhesion; Chelating Agents; Dental Prophylaxis; Dentin; Edetic Acid; Gels; Humans; Root Canal Preparation; Smear Layer; Statistics, Nonparametric; Tooth Root